2007
DOI: 10.1177/1362361307070992
|View full text |Cite
|
Sign up to set email alerts
|

Tics and Tourette syndrome in autism spectrum disorders

Abstract: Autism spectrum disorders (ASDs) are more frequently associated with tic disorders than expected by chance. Variable rates of comorbidity have been reported and common genetic and neurobiological factors are probably involved. The aim of this study was to determine the rate of tic disorders in a clinical sample (n = 105) of children and adolescents with ASDs and to describe the clinical characteristics of a group with comorbid ASDs and tics (n = 24). The overlap between tics and other repetitive movements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 27 publications
5
83
0
2
Order By: Relevance
“…Possibly, the association of high ASSQ scores and pathological doubt might reflect issues of the underlying neuro-psychology of both disorders that is being something that both disorders might have in common. Also, in our study, tics were associated with elevated ASSQ scores, which, as tics are common in ASD (Canitano & Vivanti, 2007)), should be seen as in line with the contention of Bartz (Bartz & Hollander, 2006). ASSQ scores levels that were unaccounted for by these co-morbidities are higher than those of the general population, although at a level not too far different to those of learning disorders (Ehlers et al, 1999).…”
Section: Discussionsupporting
confidence: 74%
“…Possibly, the association of high ASSQ scores and pathological doubt might reflect issues of the underlying neuro-psychology of both disorders that is being something that both disorders might have in common. Also, in our study, tics were associated with elevated ASSQ scores, which, as tics are common in ASD (Canitano & Vivanti, 2007)), should be seen as in line with the contention of Bartz (Bartz & Hollander, 2006). ASSQ scores levels that were unaccounted for by these co-morbidities are higher than those of the general population, although at a level not too far different to those of learning disorders (Ehlers et al, 1999).…”
Section: Discussionsupporting
confidence: 74%
“…In 1999, Baron-Cohen and colleagues identified 8.1 % of 37 school-aged children with autism presenting with comorbid TS [32]. Later, Canitano et al [18] evaluated a clinical sample of 105 children with ASD, observing 22 % with a tic disorder (11 % with TS and 11 % with chronic motor tics) [18]. These findings suggested that the rate of comorbidity was higher than what would have been expected by chance; however, in both reports, the small sample size limited the generalizability of findings.…”
Section: Initial Case Reports and Case Seriesmentioning
confidence: 99%
“…A recent epidemiological study estimated the global prevalence of ASD to be between 1 and 2 % [22]. To date, numerous reports have examined the relationship between ASD and TS [17,18,[23][24][25][26][27][28][29], including several populationbased studies identifying a significant relationship between TS and ASD above and beyond what would be expected by chance [17,30,31]. However, highly variable rates of comorbidity between tic disorders and ASD have been reported, ranging from 2.9 to 30.0 % [6, 9, 16•, 30-32].…”
Section: Ts and Autism Spectrum Disorders (Asd)mentioning
confidence: 99%
See 1 more Smart Citation
“…33 There may also be a connection between tic disorders and autism spectrum disorders (ASD); a clinical survey of 105 children and adolescents with ASD found that 22 percent of them also exhibited motor tics or TS. 34 However, the mechanisms linking TS to other neurodevelopmental disorders remain unknown.…”
Section: Tourette Syndrome (Ts) Is a Neurodevelopmental Disorder Defimentioning
confidence: 99%